2016
DOI: 10.1108/lht-02-2016-0014
|View full text |Cite
|
Sign up to set email alerts
|

Search engine optimization

Abstract: Purpose – The purpose of this paper is to examine the effect of, and identify core techniques of, search engine optimization (SEO) techniques applied to the web (http://lg-sl.net) and mobile (http//m.lg-sl.net) Science Land content and services at LG Sangnam Library in Korea. Design/methodology/approach – In accordance with three major SEO guidelines, ten SEO techniques were identified and applied, and their implications were extracted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 6 publications
1
10
1
2
Order By: Relevance
“…Similarly, the relationship between perceived search engine optimization and behavioral intention to use erecruitment was not significant. The results of this study deviated from past studies that found a positive relationship between perceived search engine optimization and behavioral intention to use e-recruitment (Onaifo and Rasmussen, 2013;Lee et al, 2016). Results from this study failed to show significant support for the relationship between perceived search engine optimization and behavioral intention to use e-recruitment.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Similarly, the relationship between perceived search engine optimization and behavioral intention to use erecruitment was not significant. The results of this study deviated from past studies that found a positive relationship between perceived search engine optimization and behavioral intention to use e-recruitment (Onaifo and Rasmussen, 2013;Lee et al, 2016). Results from this study failed to show significant support for the relationship between perceived search engine optimization and behavioral intention to use e-recruitment.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, the reputation of a website and the number of its search engine indexed webpages could increase its ranking (Onaifo and Rasmussen, 2013). Similarly, another study by Lee et al (2016) highlighted that SEO techniques could help increase the exposure of the specific services and the number of visitors through search engines. Moreno and Martinez (2013) further added that any SEO project should include the proper design of accessible web content, inasmuch as search engines will interpret the web accessibility achieved as an indicator of quality.…”
Section: Perceived Search Engine Optimization and Behavioral Intentiomentioning
confidence: 99%
“…Data allow for the generation of hypotheses to explain the increase or decrease in traffic from Google Search Engine (1); to see keyword performance and revise website content for better focus (2); to identify content revision opportunities by looking for queries with positions between 11 and 20 (3); to identify new content opportunities by finding all the highest impression volume keywords that are on the third SERP page, e.g., position 20 to 50 and prioritize keywords that are somewhat related, but not strongly related to existing content (4); and to identify geographic opportunities by analyzing search traffic from other countries, then those where courier delivery is offered (in case of an online store) (5). These types of data can be reused by the website owners.…”
Section: Discussionmentioning
confidence: 99%
“…Users are searching for everything. Website owners know that high visibility in search engines converts to traffic on their website [1]. Traffic gained from internet users originating from this traffic source is further converted into goals set by website owners, or transactions if the website is an online store.…”
Section: Introductionmentioning
confidence: 99%
“…Although search engine optimization (SEO) of undergraduate research is not specifically addressed, librarians and information scientists often lead efforts to increase general discoverability of scholarly publications on the public web. For example, Gasparotto (2014) and Lee et al (2016) described SEO strategies for improving discovery of online scholarly bibliographies. Ever since Arlitsch and O'Brien's (2012) study found low indexing of institutional repositories in Google Scholar, studies have investigated the presence of institutional repositories in Google or Google Scholar.…”
Section: Literature Reviewmentioning
confidence: 99%